Can Reduced Child Support Make Joint Custody Bad for Children? The Role of Economic Incentives in U.S. Divorce Law on Child Outcomes - Daniel Fernández-Kranz; Jennifer Louise Roff; Hugette Sun (Institute of Labor Economics (IZA), 2018)
This paper examines the effect of economic incentives generated by U.S. divorce and custody law on a range of child health and human capital measures. State laws vary widely in the treatment of child support under joint custody. While some states require no child support in joint custody cases, other states require fathers with joint custody to pay the same child support as those without custody. Merging family and child data from the SIPP with state-level data on economic incentives for joint custody, we find that fathers' joint custody decisions are significantly affected by the incentives generated by reduced child support. These incentives have negative effects on children's human capital development and health, with economic incentives for joint custody leading to significantly lower educational attainment as well as worse attitudes toward school and child health. Parental characteristics and time use data suggest that economic incentives for joint custody may limit children's time spent with relatively high quality mothers, as fathers pursue joint custody in response to the policy.
Keywords: J12; J13; J22; I12; I29; K36; 330; joint custody; child support; divorce; child outcomes; human capital; health behavior